2020
DOI: 10.1177/0954408920951146
|View full text |Cite
|
Sign up to set email alerts
|

Wire Electric Discharge Machining Induced Surface Integrity for Ni55.95Ti44.05 Shape Memory Alloy

Abstract: The current study unveils the variation of surface integrity aspects (micro-hardness, surface crack density, and surface characteristics) for Ni55.95Ti44.05 shape memory alloy (SMA) with wire electric discharge machining (WEDM) process parameters, namely, pulse off time, wire tension, spark gap voltage, wire feed rate and pulse on time. The experimental results reveal that micro-hardness displays direct relationship with spark gap voltage, pulse on time, and pulse off time whereas surface crack density shows d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…These findings are similar to the results reported by Bisaria and Shandilya. 6 The influence of S V on response MRR is also manifested in Figure 3. For a certain values of S ON , S OFF and W F , MRR increases gradually until the mid-point of S V and then gradually decreases.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…These findings are similar to the results reported by Bisaria and Shandilya. 6 The influence of S V on response MRR is also manifested in Figure 3. For a certain values of S ON , S OFF and W F , MRR increases gradually until the mid-point of S V and then gradually decreases.…”
Section: Resultsmentioning
confidence: 93%
“…Recently Bisaria and Shandilya (2020) 6 performed a detailed study on WEDM of Ni 55.95 Ti 44.05 . They found that micro-hardness of machined surface is directly affected by the machining parameters, i.e., spark on-time, spark off-time and spark gap voltage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows the identi ed experimental data for conducting the experiment using MINITAB 19 software. Experimental levels of parameters were selected based on the studies of Bisaria and Shandilya 2020 [31].…”
Section: Taguchi Analysismentioning
confidence: 99%
“…They tried to reveal the effect of the variable parameters of EDWC such as wire feed, pulse on and off time, spark gap voltage, wire tension on foreign element atomic content, and recast-layer thickness using the one-factor-at-a-time approach. Bisaria and Shandilya 23 investigated the various surface integrity aspects, such as micro-hardness, surface characteristics, and surface crack density while machining the NiTi shape memory alloy in the WEDM process taking into account a range of various process parameters. The results of the experiments revealed that surface crack density displays a direct relationship with a pulse on time, micro-hardness shows a direct relationship with a pulse on and off time and gap voltage, and the inverse trend shows it with pulse off time and gap voltage.…”
Section: Introductionmentioning
confidence: 99%